Prevalence of HER-2/ neu receptor amplification and its effects over prognosis of the patients with breast cancer - Melwani, Rekha; Malik, Sadaf Jabeen; Shakeel, Sobohi; Begum, Amna; Khalid, Sarwat; Ali, Syed Naqeeb (International Journal of Research in Medical Sciences, 2020)
Background: The diagnosis and prognosis of patients with breast cancer is routinely carried out with biopsy of growth by H&E staining but it is not commonly practice with various immunomarkers including HER2/neu. However HER2/neu association in breast tumour patients with prognosis has not been studied much, so this study is aim to evaluate the frequency of HER2 (human epidermal growth factor receptor) amplification and its effects over prognosis among the patients with breast cancer. Methods: After ethical approval, retrospective observational study was conducted from October 2014 to September 2017. All operated patients with biopsy proven breast cancer, the patients having any stage of disease, with sufficient data present in hospital record and patients who received neo-adjuvant chemo-therapy/radio-therapy were included. Patients unfit for surgery due to co-morbidities like cardio renal diseases and patients having insufficient hospital record or who missed follow-ups were excluded. SPSS version 20.0 was used for data analysis for data analysis with qualitative data presented as frequency and percentages. Results: A Total 120 patients, 48(40%) had HER-2/ neu positive. Among the HER2 +ve patients, 17(35.4%) had local recurrence within 03 years while 21(43.7%) cases had distant recurrence. The disease free survival rate in 03 years was observed in 22(45.83%) out of 48 HER2 +ve cases. Conclusions: Study reveals 40% patients had HER-2/neu positive expression and was associated with poor outcomes and disease free survival time period in comparison to patient with HER-2/ neu negative.